Public Governance and Security in Nuevo León: Construction of a Sectoral Index Based on the World Bank Model - Carlos Gómez Díaz de León; Oswaldo Morales González (Social Science and Human Research Bulletin, 2026)
This article constructs and applies a sectoral index to evaluate the governance of public security policy in Nuevo León. The study is based on the six dimensions of the World Bank governance model: voice and accountability, political stability and absence of violence, government effectiveness, regulatory quality, rule of law, and control of corruption. These dimensions are adapted to the public security field through indicators from official sources, public surveys, and specialized indices. The research adopts an evaluative approach: it normalizes indicators on a 0-to-1 scale, calculates a simple index with equivalent weighting, and then proposes an adjusted index using theoretical weighting inspired by Luis F. Aguilar’s concept of public governance. The simple index produced a value of 0.397, while the adjusted index reached 0.425. Both results suggest an intermediate-low level of governance in public security policy in Nuevo León. The main finding is not a complete absence of institutional capacity, but an uneven articulation among government effectiveness, legality, citizen participation, political stability, rule of law, and control of corruption. The article contributes to the debate on subnational governance by proposing a sectoral measurement applied to a specific public policy rather than evaluating governance at an aggregate governmental level.